OPTICAL TRANSMISSION DEVICE, OPTICAL MODULATOR, AND STARTUP METHOD - ISHII TOSHIO; KAMINARI KENTA (2022)
To provide an optical transmission device and the like that can shorten the startup time of the optical transmission device.SOLUTION: An optical transmission device includes: a light-emitting unit that emits an optical signal according to a bias current; and a Mach-Zehnder optical modulator that optically modulates the optical signal according to an electrical signal. The optical modulator includes: a detection unit that detects temperature in the optical modulator; and a control unit that controls the temperature in the optical modulator so that the temperature detected by the detection unit reaches a target temperature when power startup is detected.SELECTED DRAWING: Figure 2 【課題】光送信装置の起動時間を短縮化できる光送信装置等を提供する。【解決手段】光送信装置は、バイアス電流に応じて光信号を発光する発光部と、前記光信号を電気信号に応じて光変調するマッハツェンダ型の光変調器とを有する。前記光変調器は、前記光変調器内の温度を検出する検出部と、電源起動を検出した場合に、前記検出部により検出された温度が目標温度になるように前記光変調器内の温度を制御する制御部とを有する。【選択図】図２